International journal of healthcare information systems and informatics official publication of the Information Resources Management Association. (IGI Global (701 E. Chocolate Avenue, Hershey, Pa., 17033, USA), 2006)
The International Journal of Healthcare Information Systems and Informatics (IJHISI) disseminates current technological innovations and applications in the emerging field of information systems and informatics applications in the healthcare industry while directing frameworks to advancing healthcare and clinical practices and research. This journal provides practitioners, educators, and researchers with an international collection of case studies, surveys, and empirical research using qualitative approaches as well as state-of-the-art reviews, papers, and books.